Technical Efficiency Analysis of Container Terminals in Tanjung Perak, Surabaya, East Java - Bambang Eko Afiatno; Karno Dwi Joyoutomo (Journal of Developing Economies, 2022)
Container Terminals in Tanjung Perak Port is a trading center in the Eastern Indonesia Region (KTI) with a total throughput of 3.6 million TEUs in 2020. The utility/level of use of terminal facilities, consisting of the pier/berth occupancy ratio (BOR), has reached 60%. The field/yard occupancy ratio (YOR) is 65%, while the maximum utility is 70% (UNCTAD). It is necessary to explore the technical efficiency of each container terminal using the stochastic frontier analysis (SFA) because it can also capture the inefficiency effects. This study is built from the analysis of production factors in the period of 2009-2020, where the variables used are capital (k) using company asset data, labor variable (l) using data on the number of human resources, energy variable (e) using energy cost data (fuel oil/fuel, electricity, and water). The inefficiency variables are port draught (d) and loading and unloading productivity (p). The container terminal in Tanjung Perak has a relatively high technical efficiency value of 0.94. This shows that the terminal operation is quite optimum and is approaching the maximum point. The overall average elasticity is 2.01, which can be categorized as an increasing return to scale. The elasticity of assets has the most significant proportion, so it can be concluded that the port is capital intensive. Next, it's found that the higher productivity 1% increase in loading and unloading productivity, the more inefficiency with a relatively minimal value of 0.11%. Finally, an increase of 1% in depth will increase efficiency by 10.89%.